Parental Acculturation Attitudes: Direct and Indirect Impacts on Children's Second Language Acquisition. Issue 2 (17th February 2021) - Troesch, Larissa M.; Segerer, Robin; Claus-Pröstler, Nina; Grob, Alexander
ABSTRACT: The goal of the present study was to investigate the relationship between parental acculturation attitudes and second language (L2) skills and acquisition in immigrant children and to identify the mechanisms that potentially mediate between parental acculturation attitudes and children's L2 skills and acquisition. Our longitudinal study is based on a sample of 252 children with German as L2 (age t1 : M = 41 months; t2 : M = 57 months) and their parents. Research Findings : Results revealed that parental acculturation attitudes toward the country of origin negatively correlated with children's L2 skills at t1 and at t2 . Furthermore, time spent in early childcare predicted L2 skills at t1 and at t2 . Parental L2 proficiency and children's contact with German language speakers outside of childcare were related to children's L2 skills at t1 . Parental L2 proficiency mediated the relationship between parental acculturation attitudes and children's L2 skills. Practice or Policy : The findings support the importance of early childcare attendance and parental acculturation for L2 skills and acquisition in children with an immigrant background.